2014
DOI: 10.1007/s12013-014-0315-8
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-apoptotic Effect of Polypeptide from Chlamys farreri (PCF) in UVB-Exposed HaCaT Cells Involves Inhibition of iNOS and TGF-β1

Abstract: To investigate the molecular mechanisms of polypeptide from Chlamys farreri (PCF)'s anti-apoptotic effect, HaCaT cells were exposed to 20 mJ/CM(2) UVB, with or without pretreatment of TGF-β1 antagonist SB431542, inducible nitric oxide synthase (iNOS) inhibitor S-methylisothiourea sulfate (SMT), nitric oxide scavenger carboxy-PTIO, or 1.42, 2.84, and 5.69 mM PCF, or iNOS transfection (without UVB exposure). Apoptosis was confirmed with Hoechst 33258 staining; RT-PCR and western blot were used to determine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Accumulating evidence suggests a direct link between ROS production and ER stress. Previous studies showed that PCF possessed anti-oxidant and anti-apoptotic properties, and the molecular mechanisms involve ROS scavenging [10], COX-2 [11], CD95 [12], NF-B [11,13], TGF-b1 [14], iNOS [14,15], and HSP90 [15]. In this study, the effects of PCF on ER stress in HaCaT cells following UVB irradiation were investigated.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Accumulating evidence suggests a direct link between ROS production and ER stress. Previous studies showed that PCF possessed anti-oxidant and anti-apoptotic properties, and the molecular mechanisms involve ROS scavenging [10], COX-2 [11], CD95 [12], NF-B [11,13], TGF-b1 [14], iNOS [14,15], and HSP90 [15]. In this study, the effects of PCF on ER stress in HaCaT cells following UVB irradiation were investigated.…”
Section: Discussionmentioning
confidence: 90%
“…PCF is a soluble octapeptide with a molecular weight of 879 Da, consisting of 8 amino acids, namely, Pro, Asn, Ser, Thr, Arg, Hyl, Cys, and Gly. Our recent studies have demonstrated that PCF has anti-oxidative effects, which can protect human HaCaT cells from UVB irradiation via scavenging ROS apoptosis [10][11][12][13][14][15]. However, the effects of PCF on ER stress under UVB irradiation have not yet been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, PCS extract attenuates free radicals and the overproduction of ROS in HaCaT cells induced by UVB [17], and we hypothesized that PCS extract might prevent UVB-induced inflammatory response in keratinocyte cells, as it is well known that ROS directly related to NF-κB activation is a key mediator of inflammation regulating gene expression, including COX-2, iNOS, TNF-α, IL-6, IL-8, and IL-1β [8,30,31]. In keratinocyte cells, NF-κB increased the sensitivity of inflammatory response in UVB-irradiated cells and promoted inflammatory cytokine expression [7,16,[32][33][34]. Interestingly, many reports showed that phytonutrients, especially a group of phenolic and proanthocyanidins, effectively attenuated NF-κB activities [19].…”
Section: Discussionmentioning
confidence: 99%
“…NO can be produced by platelets, and although its role has been uncertain, it is generally suggested that it plays an important role in modulating platelet function (Gkaliagkousi et al, 2009). Furthermore, a high concentration of NO stimulation from iNOS plays a critical role in proapoptotic response and cell damage, yet its function in various cell types is not clear (Kolb et al, 2000;Bian et al, 2012;Han et al, 2015). The aim of our study was to investigate the effects of TNF-α on platelet apoptosis.…”
Section: Introductionmentioning
confidence: 99%